Gaps in universal health coverage in Malawi: a qualitative study in rural communities - Abiiro, Gilbert Abotisem; Mbera, Grace Bongololo; De Allegri, Manuela (BMC health services research, 2014)
In sub-Saharan Africa, universal health coverage (UHC) reforms have often adopted a technocratic top-down approach, with little attention being paid to the rural communities’ perspective in identifying context specific gaps to inform the design of such reforms. This approach might shape reforms that are not sufficiently responsive to local needs. Our study explored how rural communities experience and define gaps in universal health coverage in Malawi, a country which endorses free access to an Essential Health Package (EHP) as a means towards universal health coverage.